Effects of Natural Habitat and Season on Cursorial Spider Assemblages in Mediterranean Vineyards - Zeana Ganem; Marco Ferrante; Yael Lubin; Igor Armiach Steinpress; Moshe Gish; Rakefet Sharon; Ally R. Harari; Tamar Keasar; Efrat Gavish-Regev (Insects, 2023)
Natural habitats adjacent to vineyards are presumed to have a positive effect on the diversity of natural enemies within the vineyards. However, these habitats differ in vegetation structure and seasonal phenology and in turn could affect the species composition of natural enemies. Here, we compared the species richness and diversity and the composition of spider assemblages in several locations within three commercial vineyards and the nearby natural habitats in a Mediterranean landscape in northern Israel. We sampled spiders by means of pitfall traps in early and in late summer. Both the time in the season and the habitat (natural versus vineyard) affected spider species richness and diversity. More species were found in early summer (47) than in late summer (33), and more occurred in the natural habitat (34 species) than in the vineyards (27–31 species). Fifteen species were found exclusively in the natural habitat, and only 11 species were shared by the vineyards and natural habitat, four of which were the most abundant and geographically widely distributed species in the samples. In late summer, spider diversity in the natural habitat was higher than within the vineyards: the spider assemblages in the vineyards became dominated by a few species late in the crop season, while those of the natural habitat remained stable. Overall, the natural habitat differed in assemblage composition from all within-vineyard locations, while the three locations within the vineyard did not differ significantly in assemblage composition. Season (early vs. late summer), however, significantly affected the spider assemblage composition. This study documents the large diversity of spiders in a local Mediterranean vineyard agroecosystem. Over 60% of the known spider families in the region occurred in our samples, highlighting the importance of this agroecosystem for spider diversity and the potential for conservation biocontrol, where natural habitats may be a source of natural enemies for nearby vineyards.